Determinants of Customer Satisfaction and Its Implications on Word of Mouth in E-Commerce Industry: Case Study in Indonesia - Nova Ch. Mamuaya; Aditya Pandowo (AIBPM Publisher, 2020)
The aim of this study is to analyze the effect of several antecedents of customer satisfaction in e-commerce industry, namely web design, time saved, product variety, and delivery performance, and their consequences on customer satisfaction and word of mouth. The investigation used purposive sampling with repeat buyers as criteria. 100 samples were eligible and feasible to test after validity and reliability are concluded. The results show that website design, time saved, and delivery performance are significantly influence on customer satisfaction. In the meantime, website design, time saved, and product variety were effect on word of mouth. In addition, the result also confirms the hidden role of customer satisfaction as intervening variable partially.